2020
DOI: 10.1093/jxb/eraa131
|View full text |Cite|
|
Sign up to set email alerts
|

Re-evaluation of the nor mutation and the role of the NAC-NOR transcription factor in tomato fruit ripening

Abstract: The tomato non-ripening (nor) mutant generates a truncated 186-amino-acid protein (NOR186) and has been demonstrated previously to be a gain-of-function mutant. Here, we provide more evidence to support this view and answer the open question of whether the NAC-NOR gene is important in fruit ripening. Overexpression of NAC-NOR in the nor mutant did not restore the full ripening phenotype. Further analysis showed that the truncated NOR186 protein is located in the nucleus and binds to but does not activate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 61 publications
2
134
0
Order By: Relevance
“…NAC domain TFs were enriched among the TFs that targeted the genes whose respective proteins were more abundant in mature compared to ripe fruit. Several NAC TFs have been reported to be involved in regulating tomato [ 107 ], melon [ 95 ] and papaya [ 100 ] fruit ripening, indicating that NAC TFs role in fruit ripening is evolutionarily conserved [ 108 ]. In peach, both ACS and ACO genes, involved in ethylene biosynthesis, display NAC transcription factor binding motifs, and several NAC TFs and key fruit ripening genes display a ripening-specific expression pattern [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NAC domain TFs were enriched among the TFs that targeted the genes whose respective proteins were more abundant in mature compared to ripe fruit. Several NAC TFs have been reported to be involved in regulating tomato [ 107 ], melon [ 95 ] and papaya [ 100 ] fruit ripening, indicating that NAC TFs role in fruit ripening is evolutionarily conserved [ 108 ]. In peach, both ACS and ACO genes, involved in ethylene biosynthesis, display NAC transcription factor binding motifs, and several NAC TFs and key fruit ripening genes display a ripening-specific expression pattern [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOR encodes an NAC transcription factor that influences many more genes than RIN during fruit ripening 14 . However, unlike the natural mutant, a recent study showed that the ripening progress of knock-out mutants produced by CRISPR/Cas9 was only partly affected 15 , 16 . Formation of the Cnr mutant was caused by the increased cytosine methylation level in the promoter region of the LeSPL-CNR gene, and the epigenetic change led to a severe nonripening phenotype 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these three commercial types, a fourth, less-studied group of tomatoes comprises Mediterranean long-shelf-life landraces [21], which are characterized by their ability to keep for up to 6 months without refrigeration, small fruit (<80 g) [22][23][24], and specific culinary usages [21,25]. The alcobaça (alc) mutation [25][26][27] in the nac.nor gene [28] has been identified as the genetic factor that confers long shelf-life in some accessions of the Penjar [25] and Ramellet varieties [23], and is also likely responsible for long shelf-life in the da Serbo variety [29]. Penjar and Ramellet show important similarities in fruit and plant traits [23,25,30] and postharvest behavior [22,31,32]; although these varieties share the same market (NE Spain) and culinary uses (mainly for sauces and "pa amb tomàquet" (bread with tomato), for which the fruit is halved and rubbed into the surface of sliced bread, and then dressed with olive oil and salt), they seem to have distinct genetic identities [21].…”
Section: Introductionmentioning
confidence: 99%